The Interval of Freedom : Soviet Literature During the Thaw, 1954-1957 - Gibian, George (Book collections on Project MUSE., 1960)
When Boris Pasternaks Doctor Zhivago was published in Europe and America in 1957 and 1958, the Western world was astonished and elated. But Doctor Zhivago is not the only significant literary work to come out of Soviet Russia recently. During four extrao.